Pedagogical grammar as a frame concept for research in the field of foreign language teaching methods. Part 17. Linguistic and pedagogical grammar - Chernovaty, L. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2024)
The article deals with the correlation between linguistic (LG) and pedagogical (PG) grammars. The author considers LG as a set of data from all existing linguistic theories, and PG as information about the conditions and ways of performing grammatical actions in the process of their acquisition in the classroom. Analysing this general problem, the author outlines the range of questions that need to be answered in the course of his study. Is there a single theory of LG that can independently provide a basis for designing an adequate PG? What is the relationship between the amount and content of LG and PG information? Does the amount and type of PG depend on specific learning objectives and conditions? What are the best ways of presenting PG information for its effective use in the learning process? What factors influence the choice of presentation method? Should the structure of the PG reflect the structure of the LG? What factors influence the order in which grammatical phenomena are introduced in the process of acquiring the relevant grammatical actions in the classroom, and what determines the way in which such phenomena are grouped into organisational units of the course material (topics, units, etc.)? Having outlined the scope of these questions, in this paper the author analyses the potential of several LG models: traditional, structural, transformational and case grammar. In the authorʼs view, the traditional model of grammar, which has been used in language teaching for centuries, remains a good source of information about the surface structure of a language, but it may lack data about its functional aspect. Although structural grammar, which served as the basis for the audiolingual method, has been much criticised, the failures of this method are more related to the inadequacy of the underlying psychological  model.  While the potential of the transformational and case models of grammar is assessed positively, the paper considers them too complex to be used in the classroom without additional processing. Based on the conclusions, the author outlines the prospects for further research.